Intellectual Disability, Vulnerability and Autonomy in Brazil: An Analysis in the Context of Bioethics (Revista Iberoamericana de Bioética, 2021)
Prejudice against people with intellectual disabilities tends to be more prevalent in countries with high levels of inequality such as Brazil. The exclusionary and discriminatory social context in which such vulnerable people live is not only perpetuated by inequality but exacerbated. This theoretical study seeks to encourage reflection on the struggle for autonomy and dignity by the intellectually disabled from a bioethical perspective. The main conclusion is that State, Family and Society must tread carefully in order to avoid limiting the independence of people with intellectual disabilities. Far from excluding them, every effort should be made to include them.
Keywords: intellectual disability; bioethics; vulnerability; autonomy; dignity